PEMAHAMAN GURU PAUD TENTANG PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA 4-6 TAHUN DI PAUDQ BEKASI TIMUR - Enih Hartiani; Siti Aminah; Wulandari, Fitri; Ade Suamah; Mimi Handayani; Uswatun Hasanah; Kikin Sakinatul Kirom; Nabil, Nabil (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2025)
This study aims to describe PAUD teachers’ understanding of the social-emotional development of children aged 4–6 years in PAUDQ East Bekasi. The research employed a descriptive quantitative method using a Likert scale questionnaire. The results showed that 85% of teachers understood the basic concepts of social-emotional development and applied strategies such as role-playing, group discussion, and storytelling. However, only 62% had optimal lesson planning to support this aspect. About 78% of teachers expressed the need for further training. The findings highlight the importance of continuously strengthening teachers’ pedagogical competence to effectively and contextually support young children's social-emotional development.